Use of chickpea soaking water in dough fermentation and its effect on quality properties of loaf bread (Journal of the College of Education for Women, 2019)
This study was carried out to investigate the possibility of chickpea soaked water as a substitute for yeast in dough fermentation and its effects on sensory properties of the laboratory loaf bread. Chickpea was soaked for 24,48 and 72 hours at room temperature and used in proportion with or without yeast in dough fermentation . The results revealed that , as the percentage of soaked chickpea water substitution increased, the volume of the produced loaf bread decreased as compared with the control treatment (only yeast ).Best results were obtained by using soaked chickpea water for 24 hours in proportion of 1:1 soaked chickpea water : yeast regarding the sensory properties ,volume and leavening of the loaf bread.Keywords: chickpea soaking water ,Yeast, Lactic acid bacteria, Sensory properties, Leavening